Derivational Suffixes in the Novel “The Legend Of Sleepy Hollow” - Anak Agung, Kirana; Nugraha Putra, I G B Wahyu; Sulatra, I Komang (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
The study concerns with derivational suffixes in the novel “The Legend of Sleepy Hollow” by Washington Irving. Descriptive qualitative method were used to identify the types and process of derivational suffixes found in the data source. This study found 213 data, consist of 23 data (11%) derivational suffixes Noun to Adjective, which were: -ish, -ous, -ful. 51 data (24%) derivational suffixes Verb to Noun, which were: -ance, -er, -ion. 16 data (8%) derivational suffixes Adjective to Noun, which was: -ness. 20 data (9%) derivational suffixes Verb to Adjective, which was: -able. 101 data (47%) derivational suffixes Adjective to Adverb, which was: -ly. The last one was 2 data (1%) derivational suffixes Noun to Verb, which was: -ish. This study concluded that the most accurrence data that was found in this analysis was derivational suffixes Adjective to Adverb.